Breakthrough applications of high-entropy materials - Yeh, Jien-Wei; Lin, Su-Jien (Journal of materials research, 2018)
The concept of high-entropy alloys has been extended to ceramics, polymers, and composites. “High-entropy materials (HEMs)” are named to cover all these materials. Recently, HEMs has become a new emerging field through the collective efforts of many researchers. Basically, high mixing entropy can enhance the formation of solution-type phases for alloys, ceramics, and composites at high temperatures, and in general leads to simpler microstructure. Large degrees of freedom in composition design as well as process design have been found to provide a wide range of microstructure and properties for applications. There are many opportunities for HEMs to overcome the bottlenecks of conventional materials. In this article, several possible breakthrough applications are pointed out and emphasized for turbine blades, thermal spray bond coatings, high-temperature molds and dies, sintered carbides for cutting tools, hard coatings for cutting tools, hardfacings, and radiation-damage resistant materials. In addition, more possible breakthrough examples are briefly described.